Antithetical Minds: Eliot's Byron and Byron's Burns. Issue 1 (1st June 2021) - Phipps, Jake
Abstract : This article examines the influence which Robert Burns had on Lord Byron's poetry and his creation of the Byronic Hero, while also viewing T.S. Eliot's 1937 essay on Byron as a significant piece of Byron criticism – useful not just for its insights on Byron, but for the affinities it reveals between Byron and Burns, and in turn, what it reveals about some of Eliot's own critical and poetic practices. Eliot ranked Byron as second only to Chaucer in terms of 'readability', and praised him for his gifts as a tale-teller and his art of digression. I argue that Burns's poem 'Tam O'Shanter' was an important source for the techniques of digression and self-conscious performance found in Don Juan, as well as for Byron's conception of the Byronic Hero, where, again, 'Tam O'Shanter', and The Jolly Beggars, are particularly illuminating.